Pesan Dakwah melalui Narasi Kepahlawanan dalam Film Sri Asih - Siti Rohmah (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2026)
Sri Asih is an Indonesian superhero film that presents heroic narratives embedded with moral, social, and spiritual values relevant to contemporary da'wah. This study aims to analyze the da'wah values contained in the heroic narrative of Sri Asih and to identify how da'wah messages are conveyed through characters, conflicts, and plot development. The research employed a descriptive qualitative approach using content analysis. Primary data were obtained from the film Sri Asih (2022), while secondary data were collected from relevant literature on da'wah communication, film narratives, and popular media. Data collection techniques included documentation, observation of dialogues and scenes, and literature review. The findings reveal that the film conveys da'wah messages implicitly through the heroic journey of Alana, the main character. The identified da'wah values include self-control, courage in upholding justice, respect for women, moral responsibility, and the spirit of amar ma’ruf nahi munkar (promoting good and preventing wrongdoing). These messages are communicated through narrative and symbolic approaches that resonate with younger audiences. Therefore, Sri Asih can be regarded as an effective medium of cultural da'wah that communicates Islamic values through popular culture and visual communication adapted to contemporary societal developments.Sri Asih is an Indonesian superhero film that presents heroic narratives embedded with moral, social, and spiritual values relevant to contemporary da'wah. This study aims to analyze the da'wah values contained in the heroic narrative of Sri Asih and to identify how da'wah messages are conveyed through characters, conflicts, and plot development. The research employed a descriptive qualitative approach using content analysis. Primary data were obtained from the film Sri Asih (2022), while secondary data were collected from relevant literature on da'wah communication, film narratives, and popular media. Data collection techniques included documentation, observation of dialogues and scenes, and literature review. The findings reveal that the film conveys da'wah messages implicitly through the heroic journey of Alana, the main character. The identified da'wah values include self-control, courage in upholding justice, respect for women, moral responsibility, and the spirit of amar ma’ruf nahi munkar (promoting good and preventing wrongdoing). These messages are communicated through narrative and symbolic approaches that resonate with younger audiences. Therefore, Sri Asih can be regarded as an effective medium of cultural da'wah that communicates Islamic values through popular culture and visual communication adapted to contemporary societal developments.